Development of an Analytical Model for Determining the Magnetic Flux of Scattering through the Gears of the Stator of a Synchronous Electric Machine with a Fractional Gear Winding - A. V. Menzhinski; S. V. Panteleev; A. N. Malashin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article presents a two-dimensional finite element model of the magnetic field of a magnetic system of a synchronous electric machine with fractional gear windings. The specific features of the distribution of magnetic fluxes (main effect, edge effect, scattering) in the magnetic system have been revealed and equivalent circuits of the magnetic circuit of the electric machine under study have been constructed at different positions of the stator gear relative to the rotor poles. The necessity of taking into account the edge effect and the dependence of the scattering flux through the gears of the stator on the coordinate of the rotor position has been justified, which is reflected in the analytical model that has been developed for determining the scattering flux through the gears of the stator of a synchronous electric machine with a fractional gear winding. The adequacy of analytical expressions was verified by means of a numerical method (finite element method). The resulting calculation error is due to the assumptions made when construсting an equivalent circuit of the magnetic circuit of the electric machine under study. A slight discrepancy between the results of the analytical calculation and the numerical experiment shows that the proposed model makes it possible to solve the problem of quantifying the magnitude of the magnetic flux scattering through the gears of the stator with high accuracy. In addition, this ensures an accurate determination of the influence of the geometric parameters of the magnetic circuit on the nature of the change in the periodic function of the scattering flow through the stator gear in the shortest time, which is of an obvious practical significance. The presented analytical model can be used in the process of optimizing a synchronous electric machine with fractional gear windings.